PEMBERDAYAAN MASYARAKAT DALAM PENCEGAHAN DAN MENGATASI PENYAKIT JAMUR PADA KAKI PETAMBAK IKAN DI KELURAHAN CINDAI ALUS KABUPATEN BANJAR - Nurlailah, Nurlailah; Dwiyanti, Ratih Dewi; Insana, Aima (UPPM Poltekkes Kemenkes Banjarmasin, 2024)
Fish farming is a type of work that involves daily work in watery and wet places. Generally, fish farmers work without wearing protective equipment, which can cause their feet to become damp and wet, thus becoming a supporting factor for fungal growth.The aim of the activity is to increase public health knowledge about fungal diseases of the skin, nails and hair and reduce the morbidity rate of fungal infections by administering anti-fungal infection drugs to fish farmers in Cindai Alus, Martapura District. The methods used in this activity are pretest, delivery of material, taking nail samples and posttest. The sampling technique was purposive where samples were taken on the toenails of participants/partners who were indicated to have a fungal infection with the criteria of nail color being black, brittle and uneven and smelling. The results of Community Service showed that there was an increase in partners' knowledge about fungal infections of the skin, nails and hair based on the results of the questionnaire. After monitoring and evaluating for 2 months, it was found that there was a decrease in fungal infections, especially on the toenails and hands, from 18 people (55%) who were infected, down to 15 people (36%) who were still infected.